REPRESENTATION OF REYNHARD SINAGA IN BBC NEWS AND THE JAKARTA POST - Novi Purwaningsih; Ingatan Gulö (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2021)
This study aims to examine the way both BBC News and The Jakarta Post representing the news about Reynhard Sinaga using the theory from Van Leeuwen. This research implemented a descriptive qualitative method as it is more suitable to analyze the data. The data are in the form of words. The data were gathered from BBC News and The Jakarta Post online versions about Reynhad Sinaga rape case. The findings revealed that both media use the inclusion strategy to decide which information chosen as their base references to represent Reynhard Sinaga. This suggests that BBC UK tends to use inclusion strategy to quote statement from different parties about Reynhard Sinaga and to inform the readers about how severe his sexual assaults' cases are. Meanwhile, The Jakarta Post tends to use inclusion strategy to compare Indonesian media news in publishing his case and to give clear depiction about the difference between Reynhard Sinaga's case to other heterosexual's crime cases. Further, this research could be used as an overview for the readers about the type of strategy used by certain journalists who represent certain person, case, or an ideology through the arrangement of words that are used in text.Keywords: CDA, representation, reynhard sinaga, van leeuwen